Relationship between inflammatory and coagulation biomarkers and cardiac autonomic function in HIV-infected individuals. (October 2014) - Young, Lari C; Roediger, Mollie P; Grandits, Greg; Baker, Jason; Somboonwit, Charurut; Williams, Ian; Lundgren, Jens D; Neaton, James D; Soliman, Elsayed Z
Aim : To examine the relationship between inflammatory and coagulation biomarkers and cardiac autonomic function (CAF) as measured by heart rate variability in persons with HIV.Materials & methods : This analysis included 4073 HIV-infected persons from the Strategies for Management of Antiretroviral Therapy study. We examined the association between IL-6, high-sensitivity C-reactive protein (hsCRP) andd -dimer with heart rate variability measures (SDNN and rMSSD), both cross-sectionally and longitudinally.Results : Cross-sectional analysis revealed significant inverse associations between IL-6, hsCRP andd -dimer with SDNN and rMSSD (p < 0.01 for all comparisons). However, longitudinal analysis failed to show a significant association between baseline IL-6, hsCRP andd -dimer with change in CAF over time.Conclusion: Cross-sectionally, higher levels of inflammatory and coagulation biomarkers were associated with lower levels of CAF in the Strategies for Management of Antiretroviral Therapy trial. Although deterioration in CAF was observed during followup, baseline levels of inflammatory and coagulation markers were not predictive of the decline in CAF over time.